Investigation of heat transfer types in an automobile fog lamp with computational fluid dynamic analysis - Sokmen, Kemal Furkan; Yamankaradeniz, Nurettin; Coşkun, Salih (LLC Editorial of Journal "Light Technik" lights-nr@inbox.ru VNISI rooms 327334106 Prospect Mira Moscow 129626, 2016)
This study investigated the temperature distribution and heat transfer in an automobile fog lamp. First, a mesh independent solution was obtained. The results were compared with the literature and validated with test results. Measurements were taken from five different points by using thermocouple. Tests were applied for two hours at 24 oC. For thermal analysis, ANSYS CFX 12.1 was employed. Air flow inside the fog lamp was assumed as steady, incompressible, laminar and three-dimensional. Thermophysical property variations, buoyancy and radiation effects were taken into consideration. The radiation effect is an important heat transfer type to be considered in the temperature distribution on the lenses of automotive lighting systems. The radiation effect can have a negative influence on the lens due to the selection of unsuitable material. Despite the complexity of the bulb geometry and its non-isothermal surface conditions, general flow and heat transfer characteristics did not change. © 2016, LLC Editorial of Journal “Light Technik”. All rights reserved.
Keywords: Automotive lighting; Computational fluid dynamics (CFD); Conjugate analysis; Head lamp; Laminar natural convection; Radiation